A Participatory Water Management? - (:unkn) unknown (My University, 2013)
The 1998 South African water reform is a good example of an attempt to democratize water resource management. It created new decentralised water management bodies and openly called for the participation of all individual water users. Yet, if the reform and discourses of the time unequivocally declared the intentions of the South African water law, the conditions surrounding the implementation of the reform left many grey areas in the materialisation of active user participation objectives, almost fifteen years after their adoption . The case of the small-scale irrigation schemes developed in the country's former Bantustans is particularly worrying .
Keywords: African Research